HOUSE DESIGN VARIABLES IN PROVIDING INDOOR THERMAL COMFORT IN WARM HUMID CLIMATE - Laina Hilma Sari; Zahriah Zahriah (Journal of Architecture&ENVIRONMENT, 2020)
Building design variables in warm-humid tropics have been widely studied using various approaches. In the climate, achieving low inside air temperature is challenged by high relative humidity for providing comfort. Therefore, this study aims at finding various ways in house design to achieve naturally indoor thermal comfort. In this case, house design variables were analyzed by using  TAS (Thermal Analysis Software) building simulation software as well as supported by literature reviews. The simulations undertaken in this research used simple models to which are applied some house design variables to determine the best way to reduce inside air temperature. The simulation used the weather data of Banda Aceh city as the case study. In this article the house design variables are discussed in the following aspects: shape, house orientation, ventilation, shading, building materials, and environmental aspect.